Síntese e caracterização de biocarvões de biomassa de casca de café e de madeira de eucalipto - Veiga, Tais Regina Lima Abreu (2016)
Biochars have been demonstrated as a valuable tool for the agricultural industry, acting in the improvement of physical and chemical properties as well as carbon immobilization in the soil. However, its properties and applicability vary according to the diversity of raw matter and carbonization parameters that can be used. In this work, we studied the influence of the type of biochar and carbonization temperatures over the properties and structure of the biochars. Biochars were produced from coffee peel and Corymbia citriodora and Eucalyptus urophylla wood with four carbonization temperatures (350, 450, 550 and 900 o C). The biomasses in natura, as well as their biochars, were characterized by means of chemical and thermogravimetric analysis, as well as by Fourier Transform Infrared Spectroscopy (FTIR). The biochars were also evaluated concerning yield, nutrient content, electric conductivity, pH, cation exchange capacity and scanning electron microscopy. The analyses revealed that the structure and properties of the biochars were influenced by the type of biomass and carbonization temperature. In general, the increase in temperature promoted thermal stabilization of the materials and increase in the porosity of the biochars. All biochars presented great potential for agricultural use, however, those produced with coffee peels were the most promising, due to its structure and physical, chemical and thermal properties.